Relation of Cardiovascular Risk Factors to Right Ventricular Structure and Function as Determined by Magnetic Resonance Imaging (Results from the Multi-Ethnic Study of Atherosclerosis) - Chahal, Harjit (2010)
The impact of cardiovascular risk factors on the left ventricle is well known but their impact on right ventricle has not been studied using advanced imaging techniques. The purpose of this study was to determine the relation between cardiovascular risk factors and right ventricular (RV) structure and function and its interaction with the left ventricle. Cardiac magnetic resonance images were analyzed in 4204 participants free of clinical cardiovascular disease in the Multi-Ethnic Study of Atherosclerosis. Multivariable linear regression models were used to study the cross sectional association between individual RV parameters and risk factors. All RV parameters except ejection fraction decreased with age (p<0.0001). RV mass was positively associated with systolic blood pressure (+0.4g, p<0.0001) and high density lipoprotein (HDL) cholesterol (+0.2g, p<0.0001); inversely with diastolic blood pressure (−0.3g, p<0.0001) and total cholesterol (−0.2g, p<0.01). RV end diastolic volume was positively associated with systolic blood pressure (+1.6ml, p<0.01) and HDL cholesterol (+1.8ml, p<0.0001); and inversely with diastolic blood pressure (−2.2 ml, p<0.0001), total cholesterol (−1.4ml, p<0.0001), current smoking (−2.7ml, p<0.05) and diabetes mellitus (−3.1ml, p<0.01). RV ejection fraction was positively related with systolic blood pressure (+1.0%, p<0.0001), HDL cholesterol (+0.4%, p<0.0001) and inversely with diastolic blood pressure (−0.7%, p<0.0001). In conclusion, the mass and volumes of the right ventricle decrease with age. Cardiovascular risk factors, especially blood pressure and HDL cholesterol are associated with subclinical changes in RV mass and volumes.